BLOCKCHAIN TECHNOLOGY AND THE FUTURE OF TAX ADMINISTRATION: OPPORTUNITIES AND RISKS - Loso Judijanto; Ilham Wahyu Budiaji; Egidius Fkun (CV. Adiba Aisha Amira, 2024)
Blockchain technology offers transformational potential in various fields, including tax administration. In the context of tax administration, blockchain introduces significant opportunities such as increased transparency, efficiency, and security of tax transactions. The technology enables an immutable decentralized ledger, reduces the risk of fraud, and speeds up the audit and verification process, thereby increasing public trust in the tax system. However, blockchain implementation is also faced with various challenges. The complexity of the technology requires specialized knowledge and skills that may not yet exist in many tax administration staff. This requires substantial investment in training and education to ensure successful implementation. Integration with existing tax systems can also be a costly and time-consuming process. Other challenges include issues of security and data privacy. While blockchain offers increased security, the technology remains vulnerable to cyberattacks, especially against connected applications and hardware. In addition, the government must ensure that the use of blockchain does not compromise the confidentiality of taxpayer data. Adjustments to existing regulations are also needed to accommodate this new technology and ensure adequate legal compliance. With a comprehensive implementation strategy, cross-sector collaboration, and adjustments to the regulatory framework, blockchain has great potential to revolutionize tax administration. The government needs to make careful planning and appropriate investments to overcome these challenges and fully capitalize on the opportunities offered by this technology. These efforts can make blockchain technology the foundation for a more modern, efficient, and reliable tax system in the future.